2016
DOI: 10.1021/acs.macromol.6b01957
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Propagation Rate Coefficients of N-Containing Methacrylates: Are We Family?

Abstract: Nitrogen-containing methacrylates are a highly interesting class of monomers, yet only very limited data exist describing their propagation rate coefficients, k p. Herein, we investigate the propagation behavior of three N-containing monomers, namely 2-(N,N-diethylamino)­ethyl methacrylate (DEAEMA), 2-(N,N-dimethylamino)­ethyl methacrylate (DMAEMA), and 3-(N,N-dimethylamino)­propyl methacrylate (DMAPMAE), where we systematically vary the ester side chain with respect to spacer and branching length with the aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 30 publications
7
38
0
Order By: Relevance
“…A combination of these features is thought to contribute to the comparatively elevated kp estimate for PLA1EMA at 50 °C of 952 L•mol -1 •s -1 , which is in a similar range as other diverse non-hydroxylated and non-linear heteroatom-containing methacrylates. [47][48][49][50][51] In particular, similar values were established for four bulky tertiary amine substituted ethylmethacrylates, 48 with the kp of 2-(N,N-dimethylamino)ethyl methacrylate (DMAEMA) slightly higher, presumably related to its less encumbered tertiary amine, and the kp for 3-(N,N-dimethylamino)propyl methacrylate (DMAPMAE) clearly below the proposed family behaviour due to the additional methylene of its propyl spacer. Thus, an interpretation of bulk PLA1EMA kp behaviour is likely rooted in the proximity of its polar and steric substituents to the methacrylic group.…”
Section: Bulk Homopropagation Kineticssupporting
confidence: 60%
See 1 more Smart Citation
“…A combination of these features is thought to contribute to the comparatively elevated kp estimate for PLA1EMA at 50 °C of 952 L•mol -1 •s -1 , which is in a similar range as other diverse non-hydroxylated and non-linear heteroatom-containing methacrylates. [47][48][49][50][51] In particular, similar values were established for four bulky tertiary amine substituted ethylmethacrylates, 48 with the kp of 2-(N,N-dimethylamino)ethyl methacrylate (DMAEMA) slightly higher, presumably related to its less encumbered tertiary amine, and the kp for 3-(N,N-dimethylamino)propyl methacrylate (DMAPMAE) clearly below the proposed family behaviour due to the additional methylene of its propyl spacer. Thus, an interpretation of bulk PLA1EMA kp behaviour is likely rooted in the proximity of its polar and steric substituents to the methacrylic group.…”
Section: Bulk Homopropagation Kineticssupporting
confidence: 60%
“…In support of this claim, we found that polyester type, length, and end-group functionality did not contribute to the relative reactivity of various methacrylate macromonomers and ST copolymerization systems, 28 and other work showed that the influence of the N,N-dimethylamino substituent on bulk kp is diluted from DMAEMA to DMAPMAE. 48 Furthermore, while Siegmann et al measured a 50% increase in bulk kp for PEGEEMA (3 PEG units) compared to EEMA (1 PEG unit) at 25 °C, 33 Smolne et al found no further increase in the bulk kp of PEGMA (7-8 PEG units) compared to that reported for PEGEEMA. 34 Interestingly, the values at which the PEGylated methacrylates appear to plateau (707 and 1954 L•mol -1 •s -1 at 40 and 80 °C, respectively) are close to the values measured for PLA1EMA (780 and 1978 L•mol -1 •s -1 at 40 and 80 °C, respectively).…”
Section: Bulk Homopropagation Kineticsmentioning
confidence: 95%
“…A large collection of data obtained this way is available in the literature for a variety of monomers such as styrene, [369] acrylates, [377,419] methacrylates, [370,372,376] (meth)acrylic acid, [420][421][422][423] [427,428] In SP-PLP-EPR a single laser pulse generates a burst of radicals and their decay due to termination is followed by a time-resolved EPR apparatus.…”
Section: Propagation (K P )mentioning
confidence: 99%
“…The average molar masses (number-average molar mass M n and weight-average molar mass M w ) and the molar mass distributions (Ð = M w /M n ) were derived from the RI signal using a calibration curve based on poly(methyl methacrylate) (PMMA) or PS standards from Polymer Laboratories. For SEC-THF analysis of the homopolymers, the Mark-Houwink-Sakurada (MHWS) parameters were also used to calculate M n , M w and Ð using the following parameters: K = 3.81 Â 10 À4 and a = 0.63 (THF; 30 1C) 53 for poly(methyl acrylate) (PMA) and K = 4.98 Â 10 À5 and a = 0.73 (THF; 30 1C) 22 for PDMAEMA.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Emulsion polymerization is a process widely investigated for the synthesis of IO/polymer particles, 17 which can fulfill most of the aforementioned criteria, since particles with relatively large sizes (diameters 4100 nm) are obtained with a relatively good control of particle surface functionalization depending on the stabilizer utilized. 17,18,22 In addition, by tuning the compatibility between the inorganic and organic phases, magnetic particles exhibiting encapsulated morphology can be obtained. However, most of the examples described in the literature report composite particles with low magnetization at saturation due to low IO contents, resulting in a very slow magnetic separation.…”
Section: Introductionmentioning
confidence: 99%